Letter - Palmer, R. A.
028-0240-001 Department Agriculture Education Finance Labour Legal Propaganda Publications Statistical TELEGRAPHIC ADDRESS: "CONGRESS MANCHESTER" TELEPHONE: BLACKFRIARS 0975 (3 LINES) Co-operative Union Ltd RS/MA GENERAL SECRETARY R. A. PALMER CONSULTING SOLICITORS W.A.S. SAN GARDE LL.D., MANCHESTER D. B. MURRAY, GLASGOW Head Office HOLYOAKE HOUSE HANOVER ST MANCHESTER 4 DATE 30th July, 1936, Sir Walter Citrine, National Council of Labour, Transport House, Smith Square, LONDON, S.W.1. Dear Sir Walter, I have your letter of the 29th instant, reference HVT/FC/796, with which you send me a copy of the appeal issued by the National Council of Labour for contributions to the fund which has been established to help the Spanish workers and their families. I will bring your communication to the notice of my Executive at its next meeting, after which I will write you further. Yours sincerely, R. A. Palmer 292/946/28/240